USE OF NEW INFORMATION TECHNOLOGIES IN STUDENTS' STUDYING OF ENGLISH LANGUAGE - Y. Spivakovska (Kherson State University, 2013)
Particular use of new information technologies in teaching of future teachers of foreign languages; didactic possibilities of information technologies in teaching English language are described in the article.